2016
DOI: 10.1007/s11548-016-1425-0
|View full text |Cite
|
Sign up to set email alerts
|

Shared control of a medical robot with haptic guidance

Abstract: The validation experiment demonstrates that the shared control approach could help the surgical robot system provide stable assistance and precise performance to execute the designated surgical task. The methodology could also be implemented with other surgical robot with different surgical tools and applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…In addition, the contextual visual approach could be used to extend the capabilities of haptic training procedures based on haptic guidance to provide information about the level of force to be applied during the execution of a specific task, such as the robotassisted system presented by Meli, Pacchierotti and Prattichizzo (2016) for training needle insertion and palpation tasks or the medical robot presented by Xiong et al (2016) used for minimally invasive surgery. Moreover, previous research has shown that the haptic feedback helps users to learn a trajectory (Feygin, Keehner and Tendick, 2002;Yang, Walter and Boulanger, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the contextual visual approach could be used to extend the capabilities of haptic training procedures based on haptic guidance to provide information about the level of force to be applied during the execution of a specific task, such as the robotassisted system presented by Meli, Pacchierotti and Prattichizzo (2016) for training needle insertion and palpation tasks or the medical robot presented by Xiong et al (2016) used for minimally invasive surgery. Moreover, previous research has shown that the haptic feedback helps users to learn a trajectory (Feygin, Keehner and Tendick, 2002;Yang, Walter and Boulanger, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to fine motor skills training (such as force exertion), Sewell et al (2007) proposed the use of haptic feedback for force skills transfer, and they analyzed the transference of force skills learned in a haptic-enabled virtual environment to performance on a surgically task (drilling a bone). Meli, Pacchierotti and Prattichizzo (2016) used haptic feedback to train a needle insertion and palpation task, and Xiong et al (2016) used force feedback for basic surgical skills training by using a medical robot.…”
Section: Accepted M M a N U mentioning
confidence: 99%
“…They were applied to teleoperated systems, for instance. Xiong et al [8] present a robotic mechanism dedicated to path-following and tumour-targeting tasks with a needle, in interventional radiology. They compute both a GVF and a FRVF in the form of a potential field to guide the user towards a path or a target and keep him/her away from simulated obstacles.…”
Section: Related Workmentioning
confidence: 99%
“…Under the guidance of imaging technology or other detectors, flexible needles pass through soft tissue to complete MIS, administer local anesthetic drugs, sample blood, perform neurosurgery, achieve placement and brachytherapy, etc. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Meanwhile, percutaneous bioscopy and therapy are widely used in the prostate, lung, liver, kidney, spine, and other organs and tissues [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, needle insertion is the first step for most MIS, and the most fundamental manipulation during MIS [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Physicians and patients anticipate a high-powered needle insertion surgery system with good reliability, high accuracy, rapid recovery, less pain, high satisfaction and low cost [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The successful use of robotic-assisted operation systems such as da Vinci and ZEUS has attracted considerable interest from the medical and engineering communities [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%